Long-term follow-up of percutaneous balloon mitral valvuloplasty for mitral stenosis: an old but needed player. (4th February 2022) - Ferreira, V; Rodrigues, I; Almeida Morais, L; Cacela, D; Bernardes, L; Patricio, L; Moura Branco, L; Galrinho, A; Leal, A; Castelo, A; Garcia Bras, P; Viegas, J; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: In the era of innovative transcatheter valve interventions, percutaneous balloon mitral valvuloplasty (PBMV) remains the primary treatment option in anatomic suitable patients. Purpose: This study aimed to evaluate longterm follow-up (FU) of PBMV and to determine predictors of MACE. Methods: Between 1991 and June 2021, 202 consecutive patients underwent PBMV in a single tertiary centre. Clinical data, echocardiographic parameters, and MACE (cardiovascular mortality, need for percutaneous or surgical mitral reintervention and hospitalization for heart failure) were analysed. Predictors of MACE were determined by Cox regression analysis. Results: Mean age was 47.3 ± 13.6 years, 89.6% female, 47.3% patients presenting atrial fibrillation. Mean Wilkins score was 7.6 ± 1.4, 51.5% had mild or moderate mitral regurgitation and mean pulmonary artery systolic pressure (PASP) of 46.7 ± 17.1 mmHg. Mean pre MVA and mean mitral valve (MV) gradient were 1.1 ± 0.2 cm2 and 10.8 ± 5.6 mmHg, respectively. Successful PMBV was achieved in 89.1%. During a mean FU of 12.0 ± 8.8 years, there were 25 deaths (12.4%) and 33.3% needed MV reintervention (6.5% underwent PBMV and 29.7% needed MV surgery). At univariate analysis, previous MV intervention [HR = 1.95 (1.02–3.72), p < 0.05], Wilkins score [HR = 1.22 (1.01–1.47), p < 0.05], pre mean MV gradient≥8 [HR = 0.62 (0.38–1.00), p < 0.05], mean MV gradient after procedure [HR = 1.37 (1.19–1.58), p < 0.05] and PASP >45 mmHg [HR = 3.29 (1.13–9.55), p < 0.05] were predictors of MV reintervention. At multivariate analysis, pre mean MV gradient≥8 [HR = 0.17 (0.037–0.81), p < 0.05] and mean MV gradient after procedure were independent predictors of MV reintervention [HR = 1.74 (1.21–2.49), p < 0.05]. Wilkins score [HR = 1.29 (1.06–1.57), p < 0.05] and mean MV gradient after procedure [HR = 1.41 (1-21–1.63), p < 0.05] were independent predictors of MACE. Cumulative event-free survival at 10 and 20 years were 72.0 and 46.0%, respectively. Conclusions: PBMV remains a reliable and efficient therapeutic option of mitral stenosis, warranting event-free survival at 10 years in most patients selected for the procedure. Mean MV gradient after procedure was independent predictor of MV reintervention and MACE during follow-up.